2018
DOI: 10.47678/cjhe.v48i1.187983
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Mobilization Practices of Educational Researchers Across Canada

Abstract: Researchers are under increasing pressure to disseminate research more widely with non-academic audiences (efforts we call knowledge mobilization, KMb) and to articulate the value of their research beyond academia to broader society. This study surveyed SSHRC-funded education researchers to explore how universities are supporting researchers with these new demands. Overall, the study found that there are few supports available to researchers to assist them in KMb efforts. Even where supports do exist, they are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Even though "positive impacts on policy and practice is generally embraced as desirable by academic institutions", 71 many institutions currently lack the necessary support systems for such activities. 71,72 Among the most common institutional barriers are money and time constraints, absence of measurable targets for KTA strategies, or Personal View difficulty in communicating scientific findings. 71 Even if support for KTA exists, it has been found that researchers do not leverage these resources and spend less than 10% of their time on KTA activities.…”
Section: It Is Time To Overcome the Pseudo-dilemma Of Being An Academic Activistmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though "positive impacts on policy and practice is generally embraced as desirable by academic institutions", 71 many institutions currently lack the necessary support systems for such activities. 71,72 Among the most common institutional barriers are money and time constraints, absence of measurable targets for KTA strategies, or Personal View difficulty in communicating scientific findings. 71 Even if support for KTA exists, it has been found that researchers do not leverage these resources and spend less than 10% of their time on KTA activities.…”
Section: It Is Time To Overcome the Pseudo-dilemma Of Being An Academic Activistmentioning
confidence: 99%
“…71 Even if support for KTA exists, it has been found that researchers do not leverage these resources and spend less than 10% of their time on KTA activities. 72 It follows that universities need to increase their capacity and that of their faculty, with regards to impactful KTA work. In particular, KTA activities should be valued in promotion and tenure processes and funders could do their part by increasing dedicated resources and support.…”
Section: It Is Time To Overcome the Pseudo-dilemma Of Being An Academic Activistmentioning
confidence: 99%
See 1 more Smart Citation
“…In the discipline of education, knowledge mobilisation research has largely focused on academic and educational leaders as citizen scholars (Cooper et al, 2018), with less focus on the inclusion of students and parents. We believe our study is among the first to consider the role of parents as partners in educational research, and, given the high level of involvement of parents in inclusive education, this discipline is uniquely positioned to lead the development of innovative research methodologies, such as research priority setting, in knowledge mobilisation.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have always been expected to make their findings available for peer review (Stenhouse, 1980) but increasingly they are being expected to demonstrate the impact of their research on practice. This concern with the use of research knowledge has contributed to a burgeoning interest in knowledge mobilisation that includes planning for dissemination and use as part of the design and conduct of research (Cooper et al., 2018; Desimone et al., 2016). Some of those working within research–practice partnership (RPP) approaches (e.g., Coburn & Penuel, 2016; Penuel et al., 2020; Sjölund et al., 2022) have further argued that teachers have a role in knowledge dissemination/mobilisation (Farley‐Ripple, 2021).…”
Section: Introductionmentioning
confidence: 99%